Analysis Food Demand of Java Households with Aids Model Estimates - Roeskani Sinaga; Manuntun Paruliah Hutagaol; Sri Hartoyo; R Nunung Nuryartono (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2022)
The quantity and quality of food consumed by the community are determined by the price level and household income. Household food expenditure share is still dominated by rice commodities. The aims of this study are 1) to analyze the level of household expenditure on food in Java and (2) to analyze the expenditure elasticity and price elasticity of household food demand in Java. The data used was March 2015, 2016, and 2017 SUSENAS data. Household consumption data was estimated using the AIDS Model. The results showed that household food expenditure share for medium and low-income groups (Q3 and Q4) for urban and rural areas was more than 50 percent. This shows that the household is food insecure. The own-price elasticity for all commodities is negative and inelastic. Changes in food prices do not significantly affect changes in demand for food commodities because their elasticity is inelastic. Household food demand is more influenced by food prices than household income for food commodities except for rice commodities. Rice has elastic expenditure elasticity (means that food demand is very responsive to changes in household expenditure/income. The relationship between each commodity is almost entirely negative (complementary).